An Intuitive End-to-End Human-UAV Interaction System for Field Exploration - Jiao, Ran; Wang, Zhaowei; Chu, Ruihang; Dong, Mingjie; Rong, Yongfeng; Chou, Wusheng (Frontiers in Neurorobotics, 2020)
This paper presents an intuitional end-to-end interaction system between a human and a hexacopter Unmanned Aerial Vehicle (UAV) for field exploration in which UAV could be commanded by natural human poses. Moreover, Some LEDs equipped on UAV are used to communicate the state and intents from UAV to human as feedback throughout the interaction. A real time multi-human pose estimation system is built which can be performed with low latency maintaining the competitive performance. A robotic arm is equipped on the UAV whose kinematic and dynamic attitude models are provided by introducing the center of gravity (COG) of the vehicle. In addition, a super-twisting extended state observer(STESO)-based back-stepping controller(BSC) is constructed to estimate and attenuate complex disturbances in the attitude control system of UAV, such as wind gust, model uncertainties, etc. Also a stability analysis for the entire control system is presented based on the Lyapunov stability theory. The pose estimation system is integrated with the proposed intelligent control architecture to command UAV to execute exploration task stably. Additionally, all the components of this interaction system are described. Several simulations and experiments have been conducted to demonstrate the effectiveness of the whole system and its individual components.